Amendment of the Fertiliser Application Ordinance: Limiting nutrient surpluses effectively - Friedhelm Taube; Alfons Balmann; Jürgen Bauhus; Regina Birner; Wolfgang Bokelmann; Olaf Christen; Matthias Gauly; Harald Grethe; Karin Holm-Müller; Walter Horst; Ute Knierim; Hiltrud Nieberg; et al. (Berichte über Landwirtschaft, 2013)
Opinion of the Scientific Advisory Board on Agricultural Policy and of the Scientific Advisory Board on Fertiliser Issues respectively, at the Federal Ministry of Food, Agriculture and Consumer Protection, as well as the German Advisory Council on the Environment, regarding the amendment of the Fertiliser Application Ordinance (DüV). – – Kurzstellungnahme der Wissenschaftlichen Beiräte für Agrarpolitik (WBA) und für Düngungsfragen (WBD) beim Bundesministerium für Ernährung, Landwirtschaft und Verbraucherschutz (BMELV) und des Sachverständigenrates für Umweltfragen der Bundesregierung (SRU) zur Novellierung der "Düngeverordnung" (DüV).
Keywords: 630